2001
DOI: 10.1103/physrevlett.87.275503
|View full text |Cite
|
Sign up to set email alerts
|

Newδ(Distorted-bcc) Titanium to 220 GPa

Abstract: Structural phase transitions of a 3d transition element, titanium, have been investigated at pressures up to 220 GPa at room temperature using a monochromatic synchrotron x-ray diffraction technique. At 140 GPa, the hexagonal (omega) phase was transformed into an orthorhombic (delta) phase with a distorted bcc structure via an intermediate (gamma) phase, which has recently been proposed by Vohra and Spencer [Phys. Rev. Lett. 86, 3068 (2001)]. Both the delta and the gamma phases had a unique zigzag-chain-like s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
107
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 17 publications
19
107
3
Order By: Relevance
“…Experimentally determined transition pressure for the α-ω phase transition in pure titanium lies at room temperature between 2 and 12 GPa, depending on the experimental conditions [38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally determined transition pressure for the α-ω phase transition in pure titanium lies at room temperature between 2 and 12 GPa, depending on the experimental conditions [38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…The α → ω allotropic transformation takes place at high pressures in titanium, zirconium and hafnium as well as in their alloys [3][4][5][6][7][8][9][10]. The transition pressure, the ability of high pressure ω-phase to retain after pressure release, and the pressure interval where α-and ω-phases coexist depend on the conditions of high-pressure treatment [2,[36][37][38][39][40][41][42][43][44][45][46][47][48]. A number of SPD techniques include the application of high pressure, especially the high pressure torsion (HPT) one.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The o phase remains stable up to 116 GPa, at which point a structural phase transition to an orthorhombic (g) phase is observed, 5 followed by another orthorhombic (d) phase reported to exist at >140 GPa and to be stable up to 220 GPa. 6 It is found that the o-toa, g-to-o, and d-to-g processes are reversible on pressure release. 3,6 The high-pressure b phase has not been observed in pure titanium in most of the experiments, 4 except as claimed by Ahuja et al 7 for the observation of the o-to-b transition in the range 40-80 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…6 It is found that the o-toa, g-to-o, and d-to-g processes are reversible on pressure release. 3,6 The high-pressure b phase has not been observed in pure titanium in most of the experiments, 4 except as claimed by Ahuja et al 7 for the observation of the o-to-b transition in the range 40-80 GPa. In addition to high pressure studies, shock 8,9 and severe plastic deformation 10 experiments performed at ambient temperature only show the a-to-o phase transformation in Ti and Ti-6Al-4V alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation